2015
DOI: 10.4310/cms.2015.v13.n6.a6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the diffuse-domain method for solving PDEs in complex geometries

Abstract: Abstract. In recent work, Li et al. (Comm. Math. Sci., 7:81-107, 2009) developed a diffusedomain method (DDM) for solving partial differential equations in complex, dynamic geometries with Dirichlet, Neumann, and Robin boundary conditions. The diffuse-domain method uses an implicit representation of the geometry where the sharp boundary is replaced by a diffuse layer with thickness that is typically proportional to the minimum grid size. The original equations are reformulated on a larger regular domain and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 69 publications
(73 reference statements)
4
29
0
Order By: Relevance
“…Therefore, a lot of research has been conducted to construct accurate methods employing meshes which are not aligned with Γ but possess a "simple" structure and are fixed throughout the simulation; see for instance the immersed boundary method [42], the immersed interface method [33,37], immersed finite elements [36,39,45], the fictitious domain method [5,27,28,40], the unfitted finite element method [7,19,31,34], the finite cell method [41], unfitted discontinuous Galerkin methods [9], or composite finite elements [30,38], and the references provided there. In this work we will focus on a diffuse interface method for solving (1), see for instance [1,17,23,24,32,35,43]. In this method the sharp interface condition u = g on Γ is replaced by suitable conditions on u − g on a diffuse layer centered around Γ.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Therefore, a lot of research has been conducted to construct accurate methods employing meshes which are not aligned with Γ but possess a "simple" structure and are fixed throughout the simulation; see for instance the immersed boundary method [42], the immersed interface method [33,37], immersed finite elements [36,39,45], the fictitious domain method [5,27,28,40], the unfitted finite element method [7,19,31,34], the finite cell method [41], unfitted discontinuous Galerkin methods [9], or composite finite elements [30,38], and the references provided there. In this work we will focus on a diffuse interface method for solving (1), see for instance [1,17,23,24,32,35,43]. In this method the sharp interface condition u = g on Γ is replaced by suitable conditions on u − g on a diffuse layer centered around Γ.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Note that for DDM3, since the phase field function φ and its gradient vanish rapidly outside D, in order to prevent the equation from being ill-posed, we use the following modified gradient instead in the numerical calculation [75],…”
Section: Diffuse Domain Methods To the Poisson Equation With Dirichletmentioning
confidence: 99%
“…Using rigorous mathematical theory [71,72,73,74], matched asymptotic expansions and numerical simulations (e.g., [45,46,47,48,49]), the DDMs have been shown to converge to the original PDE and boundary conditions as the diffuse interface parameter tends to zero. Further, in [75] a matched asymptotic analysis for general DDMs with Neumann and Robin boundary conditions showed that for certain choices of the source terms, the DDMs were secondorder accurate in and in the grid size h in both the L 2 and L ∞ norms, taking ∝ h; see the recent paper [74] for a rigorous proof.…”
Section: Introductionmentioning
confidence: 98%
“…Finite element methods based on diffuse boundaries,() also known as diffuse domain, phase‐field, fat boundary, or spread interface methods, provide a pathway for solving boundary value problems on very complex domains without the need for explicitly parameterizing boundary and interface surfaces. Various instantiations related to the phase‐field concept have been published in the last few years, eg, for advection‐diffusion problems,() multiphase flow,() the evolution of complex crack patterns,() fluid infiltration and biomedical growth processes,() and phase transition and segregation processes.…”
Section: Introductionmentioning
confidence: 99%